Comparación de la abundancia, estructura de tallas y fecundidad de Voluta musica (Caenogastropoda: Volutidae) en tres sitios de la costa norte de la Península de Araya, Venezuela - Peralta, Ana Carolina (2015)
Considering the intensive artisanal fishing activity and the consequent carrion discard found at Isla Caribe, in relation to other two sites with no intensive artisanal fishing activity, we expect different effects on some features of V. musica life history (larger egg capsules, larger organisms, higher abundance of adult organisms). In this paper we compare some population parameters of Voluta musica at three localities in the north coast of the Araya Peninsula in Venezuela under different fishing exploitation regimes. The samples were taken monthly during 2008 and 2009 at Isla Caribe, Isla Lobos and Bajo Cuspe. At each site, samples were taken within three areas of 40m2. The abundance of V. musica ranged between 5 ind/120m2 to 30 ind/120m2 with significant differences between sites (F=7.77; p<0,01). Organisms from Isla Caribe were larger in size (p=0,045), than those in the other two sites. There is a significant differences in the number of egg capsules between sites and between months, and there is clear evidence that Isla Caribe has the largest abundance of egg capsules (p<0,01) suggesting that the extra feeding source (carrion) found at Isla Caribe could have a positive effect on the reproductive potential of the V. musica population at this site.